REMOTE WORK POLICIES: REDEFINING HR PRACTICES FOR THE DIGITAL ERA: REMOTE WORK POLICIES: REDEFINING HR PRACTICES FOR THE DIGITAL ERA - Yusuf, Muhammad (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2024)
This study investigates the impact of remote work policies and technological infrastructure on employee engagement and productivity at PT. Citra Mandiri Jaya Makmur. Using a quantitative approach with data collected from 75 employees, the research employs Structural Equation Modeling (SEM) with Smart PLS software to analyze the relationships between remote work implementation, technological infrastructure, employee engagement, and productivity. The results reveal significant direct effects of remote work implementation and technological infrastructure on both employee engagement and productivity, as well as a significant indirect effect of remote work implementation on productivity mediated by employee engagement. However, the indirect effect of technological infrastructure on productivity through employee engagement is found to be not significant. These findings highlight the critical role of effective remote work policies in enhancing employee engagement and productivity, while also suggesting the need for further exploration into the mechanisms underlying the relationship between technological infrastructure, employee engagement, and productivity. Overall, the study provides valuable insights for organizations seeking to optimize remote work strategies and technological investments to drive employee engagement and productivity in the digital era.